Strategi Peningkatan Kinerja Badan Amil Zakat Daerah (BAZDA) Kabupaten Nganjuk (Studi Analisis dengan Metode Balanced Scorecard) - Mukhamad Zakariya (Universitas Islam Lamongan, 2016)
To optimize the role of BAZDA, it requires good fund management strategy so as to create public confidence in disbursing the fund to Bazda rather than giving it directly to mustahik. Directly channeling is closer to the consumptive use that it somewhat obscures productive purposes. Author feel interested in doing research related to performance improvement strategy of BAZDA Nganjuk residence to the management of zakat, infaq, and sadaqah with Balanced Scorecard method. This study titled